Interest Analysis Epilachna sp. of Plant Types of Eggplant Leaves (Solanum melongena), Rimbang Leaves (Lycopersicum torvum), and Chili Leaves (Capsicum sp.) - Weyni Iskandaria (Jurnal Biologi Tropis, 2023)
The abundance, survival and reproduction of herbivorous insects are strongly influenced by changes caused by plant traits. One example is Epilachna sp.. An animal's likes or preferences can change with experience. If the availability of a particular food in the environment is low, then that type of food will be less available as food, but if the availability is higher or more abundant than usual, then that type of food will be consumed more (often). So, the main aim of this research is to find out what food preferences are most frequently attacked and eaten by Epilachna sp. and also the reasons and contents. The research method is qualitative research, meaning that the observations made by the researcher were obtained from various article references and direct observation. The feed given is eggplant leaves, rimbang leaves and chili leaves. The food that occupies the highest level is Epilachna sp. namely eggplant leaves, this is because there are nitrogen and alkaloids. The second rank which is not far from the first rank is Rimbang Leaf. Meanwhile, chili leaves occupy the lowest level or are not liked by Epilachna sp.